2013
DOI: 10.4049/jimmunol.1300596
|View full text |Cite
|
Sign up to set email alerts
|

p33 (gC1q Receptor) Prevents Cell Damage by Blocking the Cytolytic Activity of Antimicrobial Peptides

Abstract: The innate immune system is the first line of defense against invading microbes. Its specificity relies a great deal on host pattern recognition molecules that sense pathogen-associated molecular patterns of the invading pathogen. However, full protection is not always guaranteed, and some early defense mechanisms involved in bacterial killing, such as the complement system, can also exert cytolytic activity against host cells. Although these cascades are tightly regulated, the host has to take additional prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Indeed, exogenously applied trimeric p33 binds LL-37 and other HDPs. HDPs show high affinity for the negatively charged beta-sheet (aa 115-135) of p33, thereby neutralizing their antimicrobial activity [27]. p33 has been proposed to prevent HDP-induced cytotoxicity in endothelial cells and erythrocytes through this scavenging mechanism [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, exogenously applied trimeric p33 binds LL-37 and other HDPs. HDPs show high affinity for the negatively charged beta-sheet (aa 115-135) of p33, thereby neutralizing their antimicrobial activity [27]. p33 has been proposed to prevent HDP-induced cytotoxicity in endothelial cells and erythrocytes through this scavenging mechanism [27].…”
Section: Introductionmentioning
confidence: 99%
“…HDPs show high affinity for the negatively charged beta-sheet (aa 115-135) of p33, thereby neutralizing their antimicrobial activity [27]. p33 has been proposed to prevent HDP-induced cytotoxicity in endothelial cells and erythrocytes through this scavenging mechanism [27]. Moreover, exogenous p33 (1-10 µM) antagonizes LL-37-induced apoptosis in osteoblasts in a concentration-dependent manner [22].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular histones are cytotoxic against eukaryotic cells and exert hemolytic activity against human eythrocytes [27]. In the next experiment, we tested whether plasmin could prevent histone-induced hemolysis.…”
Section: Resultsmentioning
confidence: 99%
“…We also noted that a significant fraction of the histones was attached to the cell membrane. Recently, we reported that endothelial cells express a negatively charged protein, also known as p33 or globular C1q receptor, which binds to antimicrobial peptides (AMPs) and thereby protects cells from a lytic attack [16]. Like AMPs, histones are positively charged, so we decided to test whether the binding of histone H4 to the endothelial surface is also mediated by p33.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that p33 exhibits a high affinity for another group of proteins/peptides, namely AMPs. Our data show that this interaction impairs the bactericidal and cytotoxic features of AMPs and prevents AMP-evoked cell necrosis [16]. It is noteworthy that extracellular histones and AMPs have features in common [32].…”
Section: Discussionmentioning
confidence: 97%